2018
DOI: 10.1177/1753425918757898
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of innate immune viral sensors in patients following allogeneic hematopoietic stem cell transplantation

Abstract: Viral infection is a major cause of morbidity and mortality following allogeneic hematopoietic stem cell transplant (HSCT), with up to one in four deaths directly linked to viral disease. Whilst awaiting lymphocyte reconstitution post-HSCT, the innate antiviral immune response is the first line of defense against invading viruses. Several novel innate viral-sensing pathways have recently been characterized, but their physiological importance in humans is poorly understood. We analyzed a panel of innate viral-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Recent human studies have highlighted a role for HHVs in the pathogenesis of pulmonary complications after HCT (6,8,9). Viral infections after HCT cause morbidity and mortality by altering host immune responses in the lungs and other host target organs (10)(11)(12). Using a syngeneic murine transplant model, we previously reported that infections with murine gammaherpesvirus 68 (MHV-68), a mouse homolog of human Epstein-Barr virus (EBV) and Kaposi sarcoma-associated herpesvirus, given after HCT engraftment caused severe pneumonitis and lung fibrosis 3 weeks after infection, a time period when lytic viral infection was cleared (10,13).…”
mentioning
confidence: 99%
“…Recent human studies have highlighted a role for HHVs in the pathogenesis of pulmonary complications after HCT (6,8,9). Viral infections after HCT cause morbidity and mortality by altering host immune responses in the lungs and other host target organs (10)(11)(12). Using a syngeneic murine transplant model, we previously reported that infections with murine gammaherpesvirus 68 (MHV-68), a mouse homolog of human Epstein-Barr virus (EBV) and Kaposi sarcoma-associated herpesvirus, given after HCT engraftment caused severe pneumonitis and lung fibrosis 3 weeks after infection, a time period when lytic viral infection was cleared (10,13).…”
mentioning
confidence: 99%